DEVELOPMENT OF AUDIO VISUAL BASED NUMBERED HEADS TOGETHER LEARNING MODEL TO IMPROVE LEARNING OUTCOMES IN MULTIPLES AND NUMBER FACTORS - Sastra Wijaya; Ari Gunardi; Nadia Ilannur (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2021)
AbstractAudio-visual-based numbered heads together (NHT) learning model to improve the learning outcomes in multiples and number factors of mathematics subjects (This study uses a Classroom Action Research Approach for fourth grade Students of Walantaka 1 Elementary School, Walantaka District, Serang City, 2020). This research is a collaborative study between researchers, observers, and the subject under study. The purpose of this study was to improve the learning outcomes of mathematics in the fourth grade students through developing audio-visual based numbered heads together (NHT) learning models. The subjects of this research were 25 fourth grade students. The research process was carried out in three cycles. Each meeting consists of four main actions, namely planning, implementing, observing, and reflecting. At the end of each cycle a test was held using a question instrument. The results showed that the learning completeness in cycle 1 was 24%, in cycle 2 was 48%, and in cycle 3 was reached 100%. Student activeness in cycle 1 was 63.8%, increased in cycle 2 to 67.6%, and in cycle 3 reached 78.67%. The increase in the implementation of learning, in cycle 1 the score of learning implementation reached 53.2%, in cycle 2 it reached 71.6%, and in cycle 3 with an average score of learning 82.8%. This research concluded that the development of the audio-visual based numbered heads together learning model succeeded in improving students' learning outcomes in Mathematics subject of fourth grade Walantaka 1 Elementary School, Walantaka District, Serang City.Keywords: NHT, Mathematics, Multiples and Number Factors